Site índex curves for Eucalyptus urograndis stands - P. A. Mojena; S. C. Fernando; D. S. Silva; F. W. Jesus (Scientific Electronic Archives, 2019)
Site index curves were adjusted for Eucalyptus urograndis stands located in the municipality of Nova Canaã, MT, using the guide curve method. Six mathematic models were tested to estimate the dominant height of trees according to age and to verify their accuracy for the definition of site indices.The models tested presented similar values with R² values around 0.40 and errors close to 15%, without any expressive superiority in relation to others The Schumacher model was used for the construction of curves with four classes of site and with amplitude of three meters each. The model was chosen by the presented statistics, for the simplicity and adequate estimation of the heights of the trees with only two parameters, presenting the best graphical distribution of the residues.